Phytochemical Analysis, Antibacterial Activity, and GC-MS Characterization of Methanolic Extract of Azadirachta indica from Nuwakot, Nepal - Shrestha, Prabina; Acharya, Prajwal; Bhatt, Bishan Datt (Amrit Journal, 2024)
Azadirachta indica, known as Neem, is renowned for its diverse pharmacological properties. The present work was carried out to examine the bio-efficacy of the leaves of Azadirachta indica by examining phytochemical screening, GC-MS analysis, and antibacterial properties. Phytochemical screening of the extract revealed the presence of bioactive secondary metabolites like alkaloids, carbohydrates, flavonoids, tannins, steroids, and phenolic compounds. The GC-MS analysis revealed the presence of 30 compounds, among which 3- Oxatricyclo[20.8.0.0(7,16)triaconta-1(22),7(16),9,13,23,29-hexene, Phytol, 9,12,15-Octadecatrien- 1-ol, (Z, Z, Z), 3E,5E,7E-6-methyl-8-(2,6,6-trimethyl-1-cyclohexenyl)-3,5,7-octatrien-2-one, n- Hexadecanoic acid, dl-alpha,-Tocopherol, and Hexanedioic acid were found as major compounds. The antibacterial activity of the Azadirachta indica was evaluated against the Gram-positive bacterium Bacillus subtilis and the Gram-negative bacterium Enterobacter aerogenes using the filter disc diffusion technique on the Muller Hilton Agar plate (MHA). A significant zone of inhibition of 7 mm and 11 mm was observed, indicating the extract’s efficacy against both Gram-positive and Gram-negative bacteria. These findings underscore the potential of Azadirachta indica from Nuwakot district Nepal, as a source of natural bioactive compounds.